Synthesis of CdS and CdSe nanocrystallites using a novel single-molecule precursors approach - Trindade, Tito (2012)
The synthesis of CdS and CdSe nanocrystallites using the thermolysis of several dithioor diselenocarbamato complexes of cadmium in trioctylphosphine oxide (TOPO) is reported. The nanodispersed materials obtained show quantum size effects in their optical spectra and exhibit near band-edge luminescence. The influence of experimental parameters on the properties of the nanocrystallites is discussed. HRTEM images of these materials show well-defined, crystalline nanosized particles. Standard size fractionation procedures can be performed in order to narrow the size dispersion of the samples. The TOPO-capped CdS and CdSe nanocrystallites and simple organic bridging ligands, such as 2,2¢-bipyrimidine, are used as the starting materials for the preparation of novel nanocomposites. The optical properties shown by these new nanocomposites are compared with those of the starting nanodispersed materials.